(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
War and the Value of Faith, a Theological View of Freedom of Conscience.The fight for freedom is fought every day, but especially today, when technology can create real global crises. Faith that educates, and education that strengthens the main values born of faith, strengthen the transcendental relationship. Thus, in the face of global crises, the affirmation of freedom is freedom itself. The moment of silence is when freedom is willingly renounced. The era of digitalization does not elude us, but it must nevertheless be limited within the perimeter of human control. Different religious confessions struggle for the affirmation of personal beliefs, but also for the non-restriction of manifestations of worship, especially in the context of great crises. Freedom of conscience is a desire of the believer regardless of the context of the crisis, and this freedom must not be restricted no matter what. Humanity must also face contemporary challenges.